Integrative diagnosis and review of the conservation status of a Near Threatened species of the “Psalidodon scabripinnis complex” - Priscilla Caroline Silva; Karine Orlandi Bonato; Vinícius A. Bertaco; Luiz Roberto Malabarba (Neotropical Ichthyology)
Abstract The integration between morphological and barcode datasets allowed the discovery of new populations of Psalidodon cremnobates, expanding the distribution of this species to the Mampituba River drainage, municipality of Cambará do Sul, Rio Grande do Sul, Brazil and letting a review of the classification of extinction risk. DNA barcoding for these populations and other of the “Psalidodon scabripinnis complex” living in swift currents further supports the recognition of Psalidodon brachypterygium (new combination), P. cremnobates and P. laticeps as distinctive species, regardless of the lack of discrete and diagnosable ranges in body counts and measurements among them. Barcode DNA, in this sense, helps in recognizing monophyletic lineages and determining the boundaries between species with similar morphologies. The barcode divergence recommended to recognize species is also discussed.